Bibliometrics of Destination Marketing Research: Cocitation and bibliographic coupling analyses - Vo, Hong Son; Nguyen, Vuong Hoai Thao (Journal of Finance - Marketing Research, 2023)
Destination marketing is a vital domain of tourism management and research, as it involves the promotion of tourism destinations to potential visitors and the enhancement of their competitiveness and attractiveness. The aim of this study is to present a bibliometric analysis of destination marketing publications, using descriptive statistics, co-citation analysis, and bibliographic couplings. The study utilizes the Dimensions database to collect 1622 articles published in tourism and hospitality journals from 2014 to 2023. The results reveal the main trends, themes, and authors in destination marketing research, as well as the intellectual structure and development of the field. The study also identifies the research gaps and future directions for destination marketing research.